MULTIDIMENSIONAL PARADIGM OF MAQASID SHARIA IN THE BOOK OF “NAHWA TAF'ILI MAQASHID SHARIA” BY JAMALUDDIN ATHIYYAH - Aminuddin Shofi, Muhammad; Hidayatullah, Sahrul; Hamid, Abdul (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2022)
ABSTRACT This study aims to describe the concept of maqashid syariah formulated by Jamaluddin Athiyyah, especially as presented in his book Nahwa Taf'ili Maqashid Syariah. Athiyyah’s concept is unique because it divides maqashid sharia into four practical areas of life. This research combines descriptive analysis with a literature review. The primary data was collected from the book by Athiyyah, and the secondary data included books and literature from academic journals that are relevant to the research topic. Research findings indicate that Athiyyah's maqashid sharia carries a strong human spirit, which later becomes Athiyyah's rationality in developing maqashid sharia from five to twenty-four and summarized in four different dimensions: individual, family, public sphere, and humanity. The Athiyyah concept facilitates the application of maqashid sharia as a method of legal research or legal istinbath, thus can be used as a philosophical foundation (ideal norm) to analyze whether a draft law is in accordance with the objectives of Islamic law. Theoretically, this study calls for a more systematic and practical study of Athiyyah's ideas, so as to enrich the progressive and objective paradigm of Islamic law. It is recommended for Islamic law researchers to use this paradigm in empirical studies, both for enriching insights and for a test tool to what extent the effectiveness and objectivity of this theory is in the context of legal studies in Indonesia. Keywords: Humanity, Jamaluddin Athiyyah, Law, Maqashid Sharia. ABSTRAK Studi ini bertujuan untuk mendeskripsikan konsep maqashid syariah Jamaluddin Athiyyah, khususnya yang disajikan dalam buku “Nahwa Taf'ili Maqashid Syariah”. Konsep Athiyyah menjadi khas karena membagi maqahid syariah dalam empat bidang kehidupan yang lebih praktis. Riset ini menggabungkan analisis deskriptif dengan tinjauan pustaka. Sumber data primer adalah buku karya Athiyyah yang didukung dengan buku dan literatur dari jurnal-jurnal ilmiah yang relevan dengan topik riset. Temuan riset menunjukkan bahwa maqashid syariah Athiyyah membawa semangat kemanusiaan yang kuat, yang kemudian menjadi rasionalitas Athiyyah dalam mengembangkan maqashid syariah dari lima menjadi dua puluh empat dan terangkum dalam empat dimensi yang berbeda: individu, keluarga, ruang publik, dan kemanusiaan. Konsep Athiyyah memudahkan penerapan maqashid syariah sebagai metode riset hukum atau istinbath hukum, paradigma ini dapat digunakan sebagai landasan filosofis (norma ideal) untuk mengetahui apakah suatu rancangan undang-undang yang dikembangkan telah sesuai dengan tujuan hukum Islam. Implikasi riset secara teoretis adalah perlu adanya kajian lebih sistematis dan praktis tentang gagasan Athiyyah, sehingga dapat memperkaya paradigma hukum Islam yang progresif dan objektif. Direkomendasikan kepada para peneliti hukum Islam untuk menggunakan paradigma ini dalam kajian empiris, di samping untuk memperkaya wawasan, juga sebagai alat uji sejauh mana efektivitas dan objektivitas teori ini dalam konteks kajian hukum di Indonesia. Kata Kunci: Hukum, Jamaluddin Athiyyah, Kemanusiaan, Maqashid Syariah.